2022
DOI: 10.1186/s40478-022-01310-1
|View full text |Cite
|
Sign up to set email alerts
|

Acute minocycline administration reduces brain injury and improves long-term functional outcomes after delayed hypoxemia following traumatic brain injury

Abstract: Clinical trials of therapeutics for traumatic brain injury (TBI) demonstrating preclinical efficacy for TBI have failed to replicate these results in humans, in part due to the absence of clinically feasible therapeutic windows for administration. Minocycline, an inhibitor of microglial activation, has been shown to be neuroprotective when administered early after experimental TBI but detrimental when administered chronically to human TBI survivors. Rather than focusing on the rescue of primary injury with ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 60 publications
(70 reference statements)
1
9
0
Order By: Relevance
“…Previous reports from us and others have suggested that reductions in pathologic retinal inflammatory cells could be beneficial for retinal neuronal protection in a murine model of retinal I/R injury [ 13 , 32 , 33 ]. The therapeutic strategy of modulating pathologic inflammatory cells for neuroprotection can be seen in brain injury, rather than just retinal I/R injury [ 34 , 35 , 36 ]. Our current system detected reductions in pathologic retinal inflammatory cells in the NMN-treated retinas.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports from us and others have suggested that reductions in pathologic retinal inflammatory cells could be beneficial for retinal neuronal protection in a murine model of retinal I/R injury [ 13 , 32 , 33 ]. The therapeutic strategy of modulating pathologic inflammatory cells for neuroprotection can be seen in brain injury, rather than just retinal I/R injury [ 34 , 35 , 36 ]. Our current system detected reductions in pathologic retinal inflammatory cells in the NMN-treated retinas.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, using cultures of human patient-derived microglia-like cells as a model of synaptic pruning, an increased phagocytosis of synaptic elements was found in the SCZ patient-derived cells, relative to a population of cells from healthy controls (Sellgren et al, 2019). Further, this same study found that exposing cultures to minocycline, an antibiotic which normalizes microglial proinflammatory and synaptic pruning functions under certain contexts, reduced microglia-mediated synapse uptake (Scott et al, 2018;Sellgren et al, 2019;Celorrio et al, 2022). Thus, microglia have shown promise as therapeutic targets to slow the neurogenerative changes observed in SCZ, particularly as a pre-emptive measure for individuals identified as at risk of developing SCZ (Glausier and Lewis, 2013;Cannon, 2015;Sellgren et al, 2019).…”
Section: Structural Connectivitymentioning
confidence: 99%
“…Furthermore, both microglia and astrocytes play critical roles in the removal of amyloid-β (Rogers et al, 2002;Mannix and Whalen, 2012;Ries and Sastre, 2016), and thus, their hyperactivity could explain reduced amyloid-β levels in the cerebrospinal fluid of patients with DOCs (Bagnato et al, 2018). Glial cells indeed appear to be a key factor in DOC brain connectivity, so much so that clinical trials (Pizzol, 2021) have begun to investigate the effects of minocycline, which normalizes microglial functions but also shows potential in reducing chronic inflammation after traumatic brain injury, in treating DOCs (Scott et al, 2018;Celorrio et al, 2022). If administered acutely after brain injury, the pharmacological effects of minocycline include a reduction in the total number of microglia, and for the microglia that remain, a diminished major histocompatibility complex II expression (Celorrio et al, 2022) suggesting a reduction in microglia-mediated CNS inflammation.…”
Section: Structural Connectivitymentioning
confidence: 99%
See 2 more Smart Citations